Pengaruh Metode Pembuatan Tepung Ikan Beloso (Saurida Tumbil) Terhadap Nilai Gizi Dan Organoleptik Tepung Ikan Beloso (Saurida Tumbil) - Lucia Dewi Indrayani Manurung; Ahyani Ridhayani Lubis; Wahyuni Siahaan (Universitas Pahlawan Tuanku Tambusai, 2024)
Beloso fish (Saurida tumbil) is a marine fish that has an elongated body shape that can reach 40 cm, has scales, and the lateral line is above the pectoral fins. The body of this fish is silvery white on the stomach and brownish gray on the back. Beloso fish are often found in shallow coastal waters and are distributed in tropical and subtropical areas. Beloso fish is a fish that is less popular with the public. This research aims to determine the process of making beloso fish meal using a completely randomized design (CRD) with four treatments and three repetitions. Treatment 1 (A0) Control (Without temperature application), treatment 2 (A1) Boiling (80 - 90 0 C for 1 hour), treatment 3 (A2) Steaming (80- 90 0 C for 1 hour) and treatment 4 Acetone extraction (A3) (5 ml acetone in a separating funnel) to obtain 12 experimental units. Based on the results of organoleptic tests, the panelists' most preferred treatment for Beloso flour was A21 (Steaming), color characteristics with an average value of 8.87, while the average value of aroma characteristics was 8.73 and the average value of texture characteristics was 8.93. . Meanwhile, the proximate test results in treatment A01 (control) where the water content met SNI No. 01-2175-1992 with a value of 9.82 and A32 (extract) treatment had the highest protein value, namely 82.54